(untitled) (Damascus University Journal for engineering sciences, 2021)
Routing algorithms are used in computer networks to discover shortest path from source to destination. Dijkstra algorithm is mainly used to find shortest path between source and destination ,while there are algorithms that discover alternate paths and store them inside routing tables and are used in case of failure of main path, on of which is the deleted nodes algorithm. Deleted nodes algorithm is one of the recent algorithms (MIPS, K shortest paths, ROSPF and others). Deleted nodes algorithm depends on Dijikstra algorithm to compute the alternate path and the shortest one. In this paper we discuss the ability of using the two paths (main –shortest- and the alternate) at the same time and its effect on network performance.